Chronic Obstructive Pulmonary Disease In Aboriginal Patients Of The Northern Territory Of Australia: A Landscape Perspective - Heraganahally, Subash S (Int J Chron Obstruct Pulmon Dis, 2019)
BACKGROUND: The Aboriginal population of Australia has a higher burden of chronic health conditions than non-Aboriginal Australians. However, there is a paucity of data on clinical and demographic characteristics of chronic obstructive pulmonary disease (COPD) in this population. METHOD: In this retrospective study we evaluated the clinical, demographic and environmental influences in adult Aboriginal patients with COPD living in the regional and remote communities of the Northern Territory of Australia. RESULTS: There were 380 patients (49%) with a diagnosis of COPD of the 767 patients referred to specialist respiratory outreach clinics. The mean age was 57 years (56% were female) and mean±SD BMI was 24.30±7.01 kg/m(2). Smoking history was noted in 93% of the study cohort. The most common respiratory symptom was shortness of breath in 62%, and inhaled medications (salbutamol, tiotropium, salmeterol/fluticasone) were used by 79%, 44% and 58% of patients, respectively. Spirometry showed obstructive impairment (FEV(1)/FVC <0.7) in 79% (0.56±0.17), with mean FEV(1) 42% of predicted, and a bronchodilator response was present in 28.6%. Comorbid bronchiectasis was diagnosed in 49.8% along with COPD. The relationship between COPD and community demography showed a higher proportion of smokers and those with underlying bronchiectasis to have lower FEV(1)/FVC ratios. Communities with a higher proportion of asthma were younger and had higher smoking rates. Mortality increased with increasing number of exacerbations and hospital admissions. CONCLUSION: The Aboriginal population with COPD has a higher prevalence of smoking, moderate to severe airflow obstruction on spirometry and frequently co-diagnosed bronchiectasis with increased severity of ventilatory impairment.